2015
DOI: 10.1038/srep14932
|View full text |Cite
|
Sign up to set email alerts
|

Spatial nitrifications of microbial processes during composting of swine, cow and chicken manure

Abstract: Composting is a widely-used method to recycle the nutrients in livestock manure for agriculture. The spatial stratifications of microbial processes inside the manure particle that determine organic and nitrogen transformation are virtually unclear. Here, we show the evolution of the interior microenvironment of swine, cow and chicken manure by using microelectrodes during forced-aeration composting. Composting has generally been regarded as an aerobic bioprocess, however, the long-existing of a large anoxic zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…It was noted by Brinton (2006) that microorganisms producing VFAs under semi-anaerobic conditions are facultative microorganisms and hence, events of oxygen replenishment will not necessarily disturb their presence; moreover, VFAs produced serve as an energy source for consequent aerobic microbial activity, once favorable aerobic conditions return. Depending on aerobic degradation rates (and hence oxygen utilization rate), it was shown that oxygen diffusion is limited to a range of several hundred micrometers around manure particles and thus a substantial portion remains anaerobic even in well aerated systems (Wang et al, 2015). The peak of VFAs shown in the present work is related to the most active degradation phase during which it is most difficult to sufficiently maintain aerobic conditions within aggregates and micro-environments.…”
Section: Discussionmentioning
confidence: 60%
“…It was noted by Brinton (2006) that microorganisms producing VFAs under semi-anaerobic conditions are facultative microorganisms and hence, events of oxygen replenishment will not necessarily disturb their presence; moreover, VFAs produced serve as an energy source for consequent aerobic microbial activity, once favorable aerobic conditions return. Depending on aerobic degradation rates (and hence oxygen utilization rate), it was shown that oxygen diffusion is limited to a range of several hundred micrometers around manure particles and thus a substantial portion remains anaerobic even in well aerated systems (Wang et al, 2015). The peak of VFAs shown in the present work is related to the most active degradation phase during which it is most difficult to sufficiently maintain aerobic conditions within aggregates and micro-environments.…”
Section: Discussionmentioning
confidence: 60%
“…Conforme la MO fue degradada, se observó un incremento gradual del pH, pasando de ligeramente ácido a alcalino (valores entre 8.0 y 9.5 unidades). Autores como Wang et al, (2015) y Cáceres et al, (2018) atribuyen este comportamiento a la mineralización de compuestos ricos en NT (i.e proteínas, aminoácidos y péptidos) y a nitrógeno amoniacal producido durante el proceso de amonificación. Efecto de la incorporación de pasto estrella sobre el mejoramiento del proceso y la calidad del producto del compostaje de biorresiduos…”
Section: Degradación De La Materia Orgánica Durante El Procesounclassified
“…Aerobic composting shows potential for the conversion of the chicken manure into biofertilizers and reduce the potential pollution [3,4]. Whereas the characteristics of poor porosity and low C/N ratio, limit the oxygen consumption and organic matter (OM) degradation, resulting in high nitrogen loss during chicken manure composting [5]. However, the high temperature (>45˚C) reached during the composting process may help to shift the NH 4 to NH 3 [6,7] and inhibit nitrification at the same time, thereby increasing NH 3 volatilization [8].…”
Section: Introductionmentioning
confidence: 99%